1996
DOI: 10.1007/bf02358606
|View full text |Cite
|
Sign up to set email alerts
|

Expression of interferon-alpha receptor mRNA in the liver in chronic liver diseases associated with hepatitis C virus: Relation to effectiveness of interferon therapy

Abstract: To investigate whether interferon-alpha receptor (IFN-alpha Rc) expression was related to the effectiveness of interferon therapy in hepatitis C virus (HCV)-associated chronic liver disease (CLD). IFN-alpha Rc mRNA was investigated by reverse transcription polymerase chain reaction (RT-PCR) in liver biopsies and peripheral blood mononuclear cells (PBMCs) from 40 patients with HCV-associated CLD who subsequently received IFN-alpha therapy. IFN-alpha Rc mRNA in the liver was detected in 18 of 20 (90%) responders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
20
1

Year Published

2001
2001
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 37 publications
(3 reference statements)
3
20
1
Order By: Relevance
“…634,2000). Other studies have demonstrated that the IFN-␣/␤ receptor is down-regulated in HCV chronically infected patients (25,26,46). The importance of the host in IFN responsiveness was also demonstrated when the virus from an IFNunresponsive patient became responsive to IFN when transmitted to another individual (58).…”
Section: Resultsmentioning
confidence: 97%
“…634,2000). Other studies have demonstrated that the IFN-␣/␤ receptor is down-regulated in HCV chronically infected patients (25,26,46). The importance of the host in IFN responsiveness was also demonstrated when the virus from an IFNunresponsive patient became responsive to IFN when transmitted to another individual (58).…”
Section: Resultsmentioning
confidence: 97%
“…Absent or low intrahepatic IFNARmRNA levels are related to a poor response to IFN-α, to increased histological hepatitis activity and to the severity of liver fibrosis in patients with chronic hepatitis C (10)(11)(12). In addition, IFNAR-mRNA expression in liver is correlated negatively with HCV-RNA viral load and the presence of HCV genotype 1b in HCV-infected patients (13)(14)(15).…”
mentioning
confidence: 85%
“…IFNAR1-mRNA has been detected in peripheral blood mononuclear cells (PBMC) from patients with chronic hepatitis C; however, no association with response to IFN-α was demonstrable (10). Using a semiquantitative reverse transcriptase-polymerase chain reaction (RT-PCR) assay, we have analyzed IFNAR1-mRNA expression in PBMC from patients chronically infected with HCV and demonstrated its association with the IFN-α response.…”
mentioning
confidence: 99%
“…It was reported that great apes could be infected with human hepatitis viruses, but usually do not progress to cirrhosis or hepatocellular carcinomas as often seen in human (31). Therefore, we would like to speculate a possibility of formulating a useful index for predicting the long-term efficacy of IFN therapy against chronic hepatitis C virus infection (32) on the confirmation of the functional consequence of the difference.…”
Section: Phylogeny Of Hominoid and Estimation Of Human͞pan Divergencementioning
confidence: 99%